THE SEVERITY OF THE COURSE, RATHER THAN IMPAIRED EXTERNAL RESPIRATORY FUNCTION, DETERMINES THE OUTCOME OF COPD TREATMENT - V.V. Bilko (Проблеми екології та медицини)
The prevalence of bronchopulmonary diseases resulting from protracted exposure to risk factors is on the rise, with these diseases now representing a primary cause of mortality on a global scale. According to the World Health Organization (WHO), 5% of deaths occur in individuals diagnosed with severe chronic obstructive pulmonary disease. The study aims to correlate the assessment of quality of life, severity of the course, and spirometry data in patients with chronic obstructive pulmonary disease (COPD). Mateials and methods: 23 patients of the control group, 23 patients with COPD II, 11 patients with COPD III, and group E took part in the study in real conditions. All patients underwent assessment of the function of external respiration, assessment of quality of life by SF-36, SGRQ questionnaires, severity of dyspnoea and severity of symptoms - mMRC and SBP test, BODE index and predicted survival for 4 years were calculated. Results. The BODE index score shows a high score in both test groups with the recommended GOLD 2024 treatment, comparing the predicted 4-year survival with the treatment of patients with stage II and III COPD, group E analyzed that patients with a diagnosis of stage II COPD who received the recommended treatment according to GOLD2024 had a higher predicted survival than those who did not. Moderate and high correlations were found between SGRQ, SF-36, and mMRC scores, BODE index, mMRC, and 4-year prognostic survival. The assessment of the treatment received by patients with COPD stage III, group E directly interacts with the assessment of dyspnoea severity. Conclusion: the correlation analysis showed the need for an integrated approach to assessing quality of life, disease severity, dyspnoea, and symptoms. For further classification of patients, special attention should be paid to the problem of joint assessment of dyspnoea severity and COPD symptom components.